State-Owned Enterprises' Financial Losses: Causal Factors and Their Implications for Public Financial Governance in Indonesia - Hidayat, Rahmat; Jannah, Samrotul; Nugraha, Imam; Mawar Mawar (Jurnal Riset Rumpun Ilmu Sosial, Politik dan Humaniora, 2026)
Financial losses at several State-Owned Enterprises (SOEs) in Indonesia indicate significant problems in the operational management and governance of state assets. This situation not only impacts SOE business performance but also directly impacts state financial management, including transparency, accountability, and efficient budget utilization. This study aims to analyze the underlying causes of financial losses at SOEs and evaluate their impact on public financial governance in Indonesia. The method used is a literature review examining regulations, SOE financial reports, previous research, government oversight reports, and relevant academic studies. The results indicate that SOE losses generally occur due to weak internal management, decision-making that is not based on data, inefficient costs, poor governance, and inadequate government oversight. The impact on public financial governance can be seen in the increasing burden on state finances and declining public trust in the management of state assets. This study recommends strengthening the implementation of Good Corporate Governance (GCG), increasing transparency and accountability in reporting, utilizing digital technology for oversight, and comprehensive evaluation of the performance of directors and commissioners to support improvements in SOE governance and public finances.